Boron nitride quantum dots decorated ultrathin porous g-C3N4: Intensified exciton dissociation and charge transfer for promoting visible-light-driven molecular oxygen activation - Yang, Yang; Zhang, Chen; Huang, Danlian; Zeng, Guangming; Huang, Jinhui; Lai, Cui; Zhou, Chengyun; Wang, Wenjun; Guo, Hai; Xue, Wenjing; Deng, Rui; Cheng, Min; et al. (Applied catalysis. B, Environmental, 2019)
[Display omitted] •A novel photocatalyst constructed by BNQDs and UPCN was prepared.•Intensified exciton dissociation and charge transfer across BNQDs/UPCN heterostructure.•Higher photocatalytic efficiency toward molecular oxygen activation under visible light.•Mechanisms of enhanced photocatalytic activities were proposed. Graphitic carbon nitride (g-C3N4) has enormous potential for photocatalysis, but only possesses moderate activity because of excitonic effects and sluggish charge transfer. Herein, metal-free heterostructure photocatalyst constructed by boron nitride quantum dots (BNQDs) and ultrathin porous g-C3N4 (UPCN) was successfully developed for overcoming these defects. Results showed that the BNQDs loaded UPCN can simultaneously promote the dissociation of excitons and accelerate the transfer of charges owing to the negatively charged functional groups on the surface of BNQDs as well as the ultrathin and porous nanostructure of g-C3N4. Benefiting from the intensified exciton dissociation and charge transfer, the BNQDs/UPCN (BU) photocatalyst presented superior visible-light-driven molecular oxygen activation ability, such as superoxide radical (O2−) generation and hydrogen peroxide (H2O2) production. The average O2− generation rate of the optimal sample (BU-3) was estimated to be 0.25 μmol L−1 min−1, which was about 2.3 and 1.6 times than that of bulk g-C3N4 and UPCN. Moreover, the H2O2 production by BU-3 was also higher than that of bulk g-C3N4 (22.77 μmol L−1) and UPCN (36.13 μmol L−1), and reached 72.30 μmol L−1 over 60 min. This work reveals how rational combination of g-C3N4 with BNQDs can endow it with improved photocatalytic activity for molecular oxygen activation, and provides a novel metal-free and highly efficient photocatalyst for environmental remediation and energy conversion.